2018
DOI: 10.1016/j.psychres.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The Metacognitions about Gambling Questionnaire: Development and psychometric properties

Abstract: Recent research has suggested that metacognitions may play a role across the spectrum of addictive behaviours. The goal of our studies was to develop the first self-report scale of metacognitions about gambling. We conducted three studies with one community (n = 165) and two clinical (n = 110; n = 87) samples to test the structure and psychometric properties of the Metacognitions about Gambling Questionnaire and examined its capacity to prospectively predict severity of gambling. Findings supported a two facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…For example, Spada, Giustina, Rolandi, Fernie, and Caselli ( 2015 ) examined metacognitive beliefs toward gambling and showed that PGs consider gambling as a useful strategy to improve cognitive-emotional state. Finally, a very recent study indicated that specific metacognition beliefs about gambling were significantly associated with GD severity among a sample of PGs ( Caselli et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Spada, Giustina, Rolandi, Fernie, and Caselli ( 2015 ) examined metacognitive beliefs toward gambling and showed that PGs consider gambling as a useful strategy to improve cognitive-emotional state. Finally, a very recent study indicated that specific metacognition beliefs about gambling were significantly associated with GD severity among a sample of PGs ( Caselli et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…To design an intervention program for social media addiction, we referred to previous studies on Internet addiction interventions. Research has shown that metacognitive beliefs about one's thinking and self-regulation influence problematic Internet use and social media addiction (Casale, Rugai, & Fioravanti, 2018;Caselli et al, 2018;Spada, Langston, Nikcêvić, & Moneta, 2008). According to the cognitive-behavioral model, cognitive distortions such as the ruminative cognitive style are the primary cause of excessive Internet use (Davis, 2001).…”
Section: Studymentioning
confidence: 99%
“…The reliability of the CMS was determined using the ICC and Cronbach's alpha coefficient that showed acceptable testretest reliability. It is worth noting this because numerous metacognition studies have not examined test-retest reliability (Bacow et al, 2009;Larøi et al, 2009;Hsu, 2010;Cook et al, 2014;Martin et al, 2014;Bailey and Wells, 2015;Fernie et al, 2015;Kollmann et al, 2016;Kolubinski et al, 2017;Alma et al, 2018;Caselli et al, 2018;Lloyd et al, 2018). In addition, the present findings are consistent with some previous studies (Cartwright-Hatton et al, 2004;Wilson et al, 2011;Lachat Shakeshaft et al, 2020) with respect to the stability of metacognition over the period of time, although the correlation was weak (r = 0.24-0.34) (Cartwright-Hatton et al, 2004) or unstable for some domains (r = 0.24-0.90) (Wilson et al, 2011) of the metacognitive questionnaire when comparing with our test-retest (r = 0.70-0.81).…”
Section: Criterion Validity and Reliabilitymentioning
confidence: 99%